2016
DOI: 10.1007/s10646-016-1641-y
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and sublethal effects of pesticides on Chrysoperla carnea larvae (Neuroptera: Chrysopidae) and the influence of rainfastness in their degradation pattern over time

Abstract: The predator Chrysoperla carnea is a model species for the study of non-target effects of pesticides under different scenarios: registration of plant protection products under the European Union and effects of the Bt toxin. Laboratory and persistence studies were carried out with six pesticides currently used in corn crops in Spain that were applied at their maximum field recommended concentrations. The assessed end-points were larval mortality, survivorship until adult stage, duration of the larval and pupal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 38 publications
0
25
0
3
Order By: Relevance
“…Therefore, despite the ability of NE to control several pests with simultaneous outbreaks in the crop, chemical treatments are often sometimes needed to maintain key and secondary pest populations under economic thresholds and the ascertaining of their compatibility is crucial for success. Thus, toxicity and sublethal effects of pesticides on NE of horticultural pests has been extensively studied under laboratory or semifield conditions (Amor et al, 2012;Bengochea et al, 2012;Abraham et al, 2013;Döker et al, 2014;Garzón et al, 2015;Maia et al, 2016;Wanumen et al, 2016;De Bortoli et al, 2017;Fernández et al, 2017, Madbouni et al, 2017. In general, much less information is available on the compatibility of novel pesticides and NE inside commercial greenhouses.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, despite the ability of NE to control several pests with simultaneous outbreaks in the crop, chemical treatments are often sometimes needed to maintain key and secondary pest populations under economic thresholds and the ascertaining of their compatibility is crucial for success. Thus, toxicity and sublethal effects of pesticides on NE of horticultural pests has been extensively studied under laboratory or semifield conditions (Amor et al, 2012;Bengochea et al, 2012;Abraham et al, 2013;Döker et al, 2014;Garzón et al, 2015;Maia et al, 2016;Wanumen et al, 2016;De Bortoli et al, 2017;Fernández et al, 2017, Madbouni et al, 2017. In general, much less information is available on the compatibility of novel pesticides and NE inside commercial greenhouses.…”
Section: Introductionmentioning
confidence: 99%
“…According to Freitas and Morales (2009) Chrysoperla is one of the most important genus in the country, since from the 36 species of this genus, four were found in Brazil, and among these species is the C. genanigra, which was found only the muskmelon crops in the region of Mossoró RN. However, studies on selectivity to insecticides on C. genanigra are scarce and not yet published, and most studies on this genus are concentrated on the species C. externa (CASTILHOS et al, 2014) and C. carnea (MAIA et al, 2016). Thus, the conduction of research on C. genanigra, especially regarding the effect of phytosanitary products on different development stages of this insect, is essential for its conservation and introduction into agroecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…The lambda-cyhalothrin insecticide was classified as slightly harmful to third instance larvae of Chrysoperla carnea (MAIA et al, 2016), for the first instance larvae of C. externa, the same insecticide was classified as harmful in this study. Silva et al (2017) evaluating the same insecticides analyzed in this study found another classification for pimetrozine (noxious), applied in larvae of the first instance of C.…”
Section: Resultsmentioning
confidence: 50%